Pharmacokinetics and Tolerability of Anti-Hepatitis C Virus Treatment with Ombitasvir, Paritaprevir, Ritonavir, with or Without Dasabuvir, in Subjects with Renal Impairment - Khatri, Amit; Dutta, Sandeep; Marbury, Thomas C.; Preston, Richard A.; Rodrigues, Lino; Wang, Haoyu; Awni, Walid M.; Menon, Rajeev M. (Clinical pharmacokinetics, 2017)
Background The direct-acting antiviral agent (DAA) combination of ombitasvir and paritaprevir (administered with ritonavir) with (3D regimen) or without (2D regimen) dasabuvir has shown very high efficacy rates in the treatment of chronic hepatitis C virus (HCV) infection. Renal impairment, a common comorbidity in patients with chronic HCV infection, can influence the pharmacokinetics of antiviral agents and hence their efficacy and safety profiles. Objective The aim of this study was to evaluate the influence of renal impairment on the pharmacokinetics and tolerability of the 3D and 2D regimens. Methods Overall, 24 subjects, six in each of four renal function groups (normal, mild, moderate, and severe), received a single dose of the 3D and 2D regimens in separate dosing periods. Plasma and urine were analyzed to assess the effect of renal impairment on drug exposure. Results DAA exposures changed by up to 21, 37, and 50 % in subjects with mild, moderate, and severe renal impairment, respectively, versus subjects with normal renal function. Ritonavir exposure increased with the degree of renal impairment (maximum 114 %). The half-lives of DAAs and ritonavir in subjects with renal impairment were generally comparable with those in healthy subjects. No safety or tolerability concerns arose in this study. Conclusion The 3D and 2D regimens do not require dose adjustment for patients with HCV infection and concomitant renal impairment.